PEMBUATAN EDIBLE FILM DARI PATI SINGKONG SEBAGAI PENGEMAS MAKANAN - Farham HM Saleh; Arni Yuli Nugroho; M. Ridho Juliantama (Teknoin, 2017)
Edible film are plastics which can be degraded by microorgaisms and is made from renewable materials. Plastics film is made from cassava starch. Plasticizer used is sorbitol and glycerol. The purposes of this research is to determine the effect of plasticizer variation and starch weight on the characteristics of cassava starch plastic films. Cassava starch weight variation are 1,75 g, 2 g, 2,25 g at sorbitol and 3 g, 3,5 g, 4 g at glycerol and glycerol variations are 1,5 ml, 1,75 ml, and 2 ml and sorbitol variations are 1,5 g, 1,75 g, and 2 g. The reseach results showed that the interactions between starch and plasticizers are significantly effect on tensile strength and elongation of the edible film while the starch cassava weight is significantly effect on the thickness of the edible film. Tensile strength of plastic film are decreased with increasing glycerol volume sorbitol weight. While elongation of plastic film rised with increasing glycerol volume and sorbitol weight. Thickness of plastic film is increase with increasing starch weight.